a 2 b 3 c 4 d
If a , b , c , d > 0 which satisfy the equation: 3 6 a + 4 b + 4 c + 3 d = 2 5 , find the maximum value of the expression above.
Give your answer to 3 decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Don't you think instead of 12th root there should be 25th root.
Log in to reply
I've added one more line for clarity. Hope this clears things up! =D
Here is a calculus way of doing it.
First, what we want to maximise is the same as maximising a 1 2 b 6 c 4 d 3 since the answer is going to be the positive twelveth root of our expression.
So, our constrained Lagrangian is L = a 1 2 b 6 c 4 d 3 − λ ( 3 6 a + 4 b + 4 c + 3 d − 2 5 ) .
Differentiating w.r.t. a,b,c and d and equating to 0, we get
0 = 1 2 a 1 1 b 6 c 4 d 3 − 3 6 λ
0 = 6 a 1 2 b 5 c 4 d 3 − 4 λ
0 = 4 a 1 2 b 6 c 3 d 3 − 4 λ
0 = 3 a 1 2 b 6 c 4 d 2 − 3 λ
which implies(Note that λ is non zero since all a,b,c and d are.)
b = 2 9 a , c = d = 3 a plugging this in the constraint, we have a = 3 1 , b = 2 3 , c = d = 1
So, a b 3 c 4 d = 3 1 2 3 = 6 1
Problem Loading...
Note Loading...
Set Loading...
We just need to partition the terms in such a way that we can apply the AM-GM inequality .
Note that a 2 b 3 c 4 d = 1 2 a 1 2 b 6 c 4 d 3 .
We split the terms as:
3 6 a = 3 a ’s added 12 times 3 a + 3 a + … + 3 a ,
4 b = 3 2 ’s added 6 times 3 2 b + 3 2 b + … + 3 2 b ,
4 c = c + c + c + c + c , and
3 d = d + d + d .
Now we apply the inequality:
2 5 3 6 a + 4 b + 4 c + 3 d 1 2 5 / 1 2 1 6 1 ≥ ≥ ≥ ≥ 2 5 ( 3 a ) 1 2 ⋅ ( 3 2 b ) 6 ⋅ c 4 ⋅ d 3 1 2 ( 3 a ) 1 2 ⋅ ( 3 2 b ) 6 ⋅ c 4 ⋅ d 3 6 a 2 b 3 c 4 d a 2 b 3 c 4 d
The maximum value of the desired expression is 6 1 ≈ 0 . 4 0 8 , and it occurs when 3 a = 3 2 b = 4 c = 3 d or a = 3 1 , b = 2 3 , c = d = 1 .